Mecanismos envolvidos na resposta inflamatória e resolutiva em um modelo murino de gota: papel de MIF e da Anexina A1 - Izabela Galvão (2015)
Gout is an inflammatory disease caused by deposition of monosodium urate (MSU) crystals into the joints. The recognition of MSU crystal induces a local inflammatory response, triggers the activation of NLRP3 inflammasome and release of IL-1β that drives the recruitment of neutrophils. Macrophage migration inhibitory factor (MIF) is a potent pro-inflammatory cytokine known to activate CXCR2 and to induce recruitment of neutrophils and plays an important role in the pathogenesis of numerous inflammatory diseases. Annexin A1 (AnxA1) have been shown to modulate biological events, restrains leukocyte recruitment and transmigration during inflammation and induces neutrophil apoptosis and efferocytosis, which are crucial events on resolution of inflammation process. The aim of this work was to evaluate the inflammatory and resolutive mechanisms in a murine model of gout. Methods and results: Experiments were performed in male C57/Bl6 and wild-type and AnxA1-/- Balb/c mice. MSU crystals injection increased MIF expression in the beginning of inflammation on synovial tissue (ELISA) and recombinant MIF injection caused neutrophil influx to articular cavity and increase the levels of IL-1β an CXCL1.The inhibition of MIF activity (ISO-1) was effective in reduction neutrophil recruitment, IL-1β levels and hypernociception. Injection of rMIF induced IL-1β mRNA synthesis both in vitro and in vivo and the inhibition of MIF activity decreased IL-1β synthesis following MSU crystals injection. However, blockade of IL-1β did not reduce the recruitment of neutrophils induced by MIF. In patients with acute gout, MIF was detectable in synovial fluid and there was a positive correlation with IL-1β levels. The evaluation of the role of AnxA1 in the inflammation induced by MSU crystals showed that AnxA1 levels in synovial tissue are directly associated with leukocyte infiltration. The inhibition of AnxA1 using two different strategies (BOC-1 and Anti-AnxA1) prevented the spontaneous resolution of gout as observed by persistence of neutrophils in the cavity at 24h time point. AnxA1-/- mice presents higher recruitment and retention of neutrophils in the joint cavity after MSU injection comparing to wild type mice, though both resolve the inflammation at 36 hours after MSU injection. The treatment with Ac2-26 (AnxA1-active N-terminal peptide) decrease the number of neutrophils recruited, shortened resolution interval (improved resolution indices) and decreased IL-1β levels. The proresolving effect of Ac2-26 was due to increased apoptosis of neutrophil since it was prevented by a pan-caspase inhibitor zVAD-fmk. Conclusion: In the model used in this study, MIF promotes neutrophil recruitment and IL-1β synthesis, two crucial events that contribute to the pathogenesis of gout. We also show that AnxA1 has an anti-inflammatory and proresolving role in inflammation induced by MSU crystals, suggesting the Ac-2-26 an important therapeutic strategy.